2018
DOI: 10.1039/c8gc00543e
|View full text |Cite
|
Sign up to set email alerts
|

Bio-electrochemical conversion of industrial wastewater-COD combined with downstream methanol synthesis – an economic and life cycle assessment

Abstract: Herein, a techno-economic and environmental performance evaluation (i.e. Life Cycle Assessment (LCA)) of a 45 kW Microbial Electrolysis Cell system is presented in the context of industrial wastewater conversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…In such cases, a full exploitation of the microbial potential is not necessary and low-cost standard commercial materials (carbon felts, ceramic separators) perform satisfactorily. In contrast, large scale wastewater/remediation applications (Hiegemann et al, 2016;Lu et al, 2017b;Wang et al, 2017) or high-tech applications such as the production of specialty chemicals (Raes et al, 2016;Streeck et al, 2018) are not yet ready for marketing, because here, high efficiencies are mandatory for economic operation and competitiveness with established technologies.…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, a full exploitation of the microbial potential is not necessary and low-cost standard commercial materials (carbon felts, ceramic separators) perform satisfactorily. In contrast, large scale wastewater/remediation applications (Hiegemann et al, 2016;Lu et al, 2017b;Wang et al, 2017) or high-tech applications such as the production of specialty chemicals (Raes et al, 2016;Streeck et al, 2018) are not yet ready for marketing, because here, high efficiencies are mandatory for economic operation and competitiveness with established technologies.…”
Section: Introductionmentioning
confidence: 99%
“…There are limited studies on the LCA of MEC. Streeck et al . demonstrated that the use of low‐cost materials in MECs has greater potential to reduce the cost compared with using expensive high‐performance materials to lower the internal resistance and polarization losses.…”
Section: Research Advancesmentioning
confidence: 99%
“…135 There are limited studies on the LCA of MEC. Streeck et al 136 demonstrated that the use of low-cost materials in MECs has greater potential to reduce the cost compared with using expensive high-performance materials to lower the internal resistance and polarization losses. LCA indicated that a waste-based process was superior to fossil-based methanol synthesis in terms of global warming potential and cumulated fossil energy demand.…”
Section: Life Cycle Assessment Techno-economic Analysis and Commercimentioning
confidence: 99%
See 1 more Smart Citation
“…The overall environmental impacts of the MEC systems increased with the increase of the applied external voltage, while decreased with the increase of the recovered hydrogen production and the 97 electricity transformation efficiency. The environmental impacts of MEC system producing/recovering chemicals other than hydrogen were reported, such as methanol [253], hydrogen peroxide [254,255], ammonium [256], etc., and demonstrated the environmental benefits compared to the conventional synthesis method. However, this was not discussed in this paper considering they were out of scope of the current study.…”
mentioning
confidence: 99%